STRATEGI PEMASARAN AYAM PROBIO (broiler) PADA KELOMPOK PETERNAK AYAM (KPA) BERKAT USAHA BERSAMA (BUB) KOTA METRO - Nyoman Sulindre; Djoko Umar Said; Zulkarnain Zulkarnain (Journal of Food System & Agribusiness, 2018)
The cultivation and processing of chicken probio (broiler) in LampungProvince was initiated by Kelompok Peternak Ayam (KPA) Berkat Usaha Bersama (BUB) in Metro City. KPA BUB was established on March 22, 2008 with members of 30 farmers. KPA BUB acts as a facilitator for its members. This study aims to analyze the Probio Chicken Marketing Strategy (Broiler) in Kelompok Peternak Ayam (KPA) Berkat Usaha Bersama (BUB) Metro City. The problem to be analyzed is how the marketing strategy is implemented by Chicken Breeder Group (KPA) Berkat Usaha Bersama (BUB) Metro City. The method used in this research was non probability sampling, that is snowball sampling technique with population of 30 probio chicken breeders. The number of sample were 25 respondents consisting of 20 farmers and 5 practitioners. Analysis tool used in this research was a descriptive analysis using SWOT analysis technique. Primary and secondary data were used. The results of this study showed that the SWOT matrix obtained coordinates (0.32, 0.37), i.e. the Strengh-Opporturnities (SO) strategy, in which the coordinates were entered in Quadrant I. Strategies that can be used are 1) Developing probio chicken products and good service to consumers by seeing the growing market growth would increase the number of probio chicken production; 2) Good service to consumers, the quality of products, and the sales cycle increased with the increasing pattern of consumer behavior that would develop the needs of the society of probio chicken consumption, 3) The strength of business and good management by utilizing a strategic plant location for promotion / advertising would increase the amount of production so the community needs for chicken probio can be met.Keywords: marketing strategy, probio chicken (broiler).